Model Perencanaan Dan Penganggaran Dana Desa Dalam Akselerasi Sustainable Development Goals Desa - Tyas, B. Hari Saptaning; Puspitasari, Condrodewi; Suban Ballol, Pius (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2025)
In 2020, the Government issued the SDGs Desa program with 18 goals whose funding is supported by the village fund. The urgency of this research is to find a model of village fund planning and budgeting in accelerating the achievement of the SDGs Desa program in Sumbermulyo Village, Bantul, DI Yogyakarta. The planning and budgeting of the village fund by the Sumbermulyo Village Government is interesting to be researched to formulate a village fund planning and budgeting model based on the acceleration of the SDGs Desa program. This study used a qualitative descriptive method. Data was collected through observation, interviews, and Focus Group Discussions (FGD). The research data was analyzed to described the used of village fund, the implementation of the SDGs Desa program and formulate a village fund planning and budgeting model in accelerating the achievement of the SDGs Desa program. The result of this study is that the planning and budgeting of the village fund in Sumbermulyo is carried out with a governance centripetal model, in addition to using a technocratic approach to planning and budgeting the village fund because it is also based on the mandate of Permendesa PDTT No.21/2020.